On transformation formulae of ordinary hypergeometric series - Yadav, Keshav; Kumar, Adarsh; Khan, Mohd Sadiq (Global Journal of Mathematical Analysis, 2014)
In this paper, making use of some well-known summation formulae and generating relations due to Qureshi, Khan and Pathan, an attempt has been made to establish some transformation formulae of ordinary hyper geometric series which are seemed to be new and in different form. We have also given some special cases.Keywords: Summation Formulae, Ordinary Hyper geometric Series, Transformation Formulae, Generating Relation.